Sintering the feasibility improvement and mechanical property of UHMWPE via selective laser sintering. (15th March 2020) - Zhu, Xiaokang; Yang, Qi
ABSTRACT: Selective laser sintering (SLS) is a branch of additive manufacturing based on powders. The research was carried out to demonstrate the sintering feasibility of ultra-high molecular weight polyethylene (UHMWPE) and the evaluation of the parts of the mechanical property prepared by SLS at various laser powers was also conducted. Meanwhile, the morphology of the parts was examined through scanning electron microscopy. Additionally, products with high three-dimensional stability were obtained via SLS with UHMWPE/SiO2 . The effects of silica and laser power on the products' relative density, dimensional accuracy and tensile property were then discussed. The incorporation of the silica reduces the difficulties in sintering the UHMWPE powder and eliminates the slice slides (layer slides between two closely packed layers) in the sintering process. However, the mechanical property decreased with the addition of the SiO2 into the powder. Meanwhile, the properties of parts show high relevance with the laser power.